With or without the EU Constitutional Treaty : towards a common security and defence policy? - Trybus, Martin (European law review, 2006)
Abstract (s. 145).
Keywords: yhteinen ulko- ja turvallisuuspolitiikka; Euroopan unionin perustuslaki